กลยุทธ์การให้บริการของสายการบินต้นทุนต่ำเพื่อให้เกิดความได้เปรียบทางการแข่งขันในอุตสาหกรรมการบิน (THE LOW COST CARRIER’STRATEGY TO GAIN AN ADVANTAGE COMPETITION IN AVIATION INDUSTRY) - Prakobkandee, Nutthapong (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2013)
ในช่วงหลายปีที่ผ่านมาธุรกิจสายการบินต้นทุนต่ำมีแนวโน้มที่จะเติบโตได้ดีในอนาคต เนื่องจากรูปแบบการให้บริการของสายการบินต้นทุนต่ำนั้นจะแตกต่างจากการให้บริการของสายการบินปกติที่มุ่งเน้นการบริการแบบหรูหรา สะดวกสบายและมีราคาค่าโดยสารที่สูง แต่รูปแบบการให้บริการของสายการบินต้นทุนต่ำนั้นจะมุ่งเน้นไปที่การทำงานที่มีประสิทธิภาพ ลดการบริการหรือสิ่งอำนวยความสะดวกที่ไม่จำเป็นออกไปเพื่อลดต้นทุน ทำให้สามารถกำหนดอัตราค่าโดยสารให้ราคาต่ำมากๆ ได้ จึงเป็นปัจจัยสำคัญที่กระตุ้นให้มีผู้โดยสารเข้ามาใช้บริการเพิ่มมากขึ้น อีกทั้งภาครัฐบาลยังให้การส่งเสริมธุรกิจสายการบิน ทั้งภายในประเทศและระหว่างประเทศตามนโยบายเปิดน่านฟ้าเสรี ดังนั้นจึงจำเป็นอย่างยิ่งที่ผู้ประกอบการในปัจจุบันจะต้องเข้าใจลักษณะพฤติกรรมและปัจจัยที่มีผลต่อการตัดสินใจเลือกใช้บริการสายการบินต้นทุนต่ำ เพื่อผู้ประกอบการจะได้สามารถกำหนดกลยุทธ์ให้สอดคล้องกับความต้องการของผู้โดยสารให้มากที่สุด คำสำคัญ: สายการบินต้นทุนต่ำ สายการบินปกติ During many recent years, the low cost carriers business has grown significantly, and it is likely to grow well in the future due to its service form provided. The low cost airline business provides the customers’ services with low cost that is different from the full-service carriers business’s service form that focuses on the luxurious and comfortable services with the high cost. However, the low cost airline business’s service form focuses on the effectiveness in order to reduce the capital. As a result, the low cost airline business is able to lower price dramatically. This can be the significant factor that can stimulate the customers to use much more its service. Furthermore, the government sector also supports this business well both domestic and international flight through air deregulation. Therefore, it is very crucial that the current entrepreneurs of this business should understand the behaviors and the factors that affect the customers’ service choosing towards the low cost airline business in order to implement business strategies for the utmost customers’ satisfaction. Keywords: Low-cost Carriers, Full-service Carrier